Changes of eye’s functions among patients with age-related macular degeneration during the use of vitamin D medications - T. M. Komarova; O. P. Vitovska; Yu. I. Komisarenko; Sibylle K. Scholtz (Сучасні медичні технології)
Aim. To increase the effectiveness of the treatment of age-related macular degeneration (AMD), dry form, in postmenopausal women by determining the level of serum vitamin D and correcting its deficiency.